Governing multisectoral action for health in low- and middle-income countries. - Kumanan Rasanathan; Sara Bennett; Vincent Atkins; Robert Beschel; Gabriel Carrasquilla; Jodi Charles; Rajib Dasgupta; Kirk Emerson; Douglas Glandon; Churnrurtai Kanchanachitra; Pete Kingsley; Don Matheson; et al. (PLoS Medicine)
Kumanan Rasanathan and colleagues argue that the potential of multisectoral collaboration for improving health remains untapped in many low- and middle-income countries.